2019
DOI: 10.1007/s10342-019-01170-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of zones with high potential for biological diversity on dormant forested landslides

Abstract: Landslides and erosion processes cause a high level of morphological diversity which, over the course of time, results in an increased level of forest species and habitat biodiversity. According to the principles of landscape ecology, information concerning points of convergence-understood as transition zones between elementary parts of a slope-could be interpreted as a surrogate for biodiversity. To recognize locations of land surface disruption, points of convergence derived from a high-resolution digital el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…These works specifically suggested that geodiversity was, or could be a possible, defining criteria in the distribution and/or abundance of marshland taxa [23], invertebrates [24,25], plants [26][27][28][29][30][31], and marine taxa [32], primarily in a qualitative sense. Newer research was more quantitative in nature, and considered geodiversity parameters such as soil textural variation and landform rugosity as a component of species and habitat distribution modelling [33][34][35][36][37][38].…”
Section: Geodiversity Biodiversity and Ecosystem Servicesmentioning
confidence: 99%
“…These works specifically suggested that geodiversity was, or could be a possible, defining criteria in the distribution and/or abundance of marshland taxa [23], invertebrates [24,25], plants [26][27][28][29][30][31], and marine taxa [32], primarily in a qualitative sense. Newer research was more quantitative in nature, and considered geodiversity parameters such as soil textural variation and landform rugosity as a component of species and habitat distribution modelling [33][34][35][36][37][38].…”
Section: Geodiversity Biodiversity and Ecosystem Servicesmentioning
confidence: 99%
“…A pesar de que en el ecotono hay una mayor cantidad de especies que podrían tener la capacidad de sobrevivir en ambientes con menos intensidad de luz (Dezzotti et al 2021), el efecto de la alta cobertura de P. ponderosa inhibió su crecimiento y desarrollo de la misma manera que a las plantas de la estepa. La mayor riqueza de familias y especies en el ecotono, en comparación con la de la estepa, se debería a la convergencia de la distribución de plantas con adaptaciones diferentes a la aridez en esta área de transición ambiental (Farina 2006;Walz 2011;Tracz et al 2019). Sin embargo, la menor dominancia de especies en la estepa, asociada a la menor equitatividad, determinó una diversidad equivalente en ambos tipos de vegetación.…”
Section: ₁₀₀₀ Ha B������ � a D�������unclassified
“…Collecting forest biodiversity data by remote sensing technology was applied in numerous studies and is considered broad-scale, accurate, and more cost-effective and faster than field sampling [40,41,45,59,68,113,[117][118][119]. Ozdemir et al [45] used satellite images to predict bird species richness and micro-habitat diversity in brutian pine (Pinus brutia) forest ecosystems in Turkey.…”
Section: Remote Sensingmentioning
confidence: 99%